2020
DOI: 10.1128/iai.00919-19
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Elaborates Persistent and Prolonged Competent State during Pneumonia-Derived Sepsis

Abstract: The competence regulon of pneumococcus regulates both genetic transformation and virulence. However, competence induction during host infection has not been examined. By using the serotype 2 strain D39, we transcriptionally fused the firefly luciferase (luc) to competence-specific genes and spatiotemporally monitored the competence development in a mouse model of pneumonia-derived sepsis. In contrast to the universally reported short transient burst of competent state in vitro, the naturally developed competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 63 publications
(115 reference statements)
6
29
0
Order By: Relevance
“…3) indicates that the environment of the nasopharynx overrides any potential products that pre-conditioning produces during activation of the QS circuit. On a similar note, it was recently shown that although the competence quorum sensing system in S. pneumoniae is activated in the murine respiratory tract, addition of activating CSP peptide pheromone was unable to induce competence in vivo [38].…”
Section: Discussionmentioning
confidence: 93%
“…3) indicates that the environment of the nasopharynx overrides any potential products that pre-conditioning produces during activation of the QS circuit. On a similar note, it was recently shown that although the competence quorum sensing system in S. pneumoniae is activated in the murine respiratory tract, addition of activating CSP peptide pheromone was unable to induce competence in vivo [38].…”
Section: Discussionmentioning
confidence: 93%
“…5A). It also challenges the idea that competence is constitutively expressed by individual bacteria in the host (Lin et al, 2020), but rather that there are pockets of pneumococci inducing competence during infection (Fig. 5).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, competence is also activated when cells are adhering to human epithelial cells (Aprianto et al, 2016), and during invasive disease as shown in several mouse and zebrafish models (Lin et al, 2020; Schmidt et al, 2019)(Jim et al, 2022). Indeed, competence development is a key pathogenic factor in pneumococcal meningitis (Jim et al, 2022; Schmidt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%